Net Electron Capture in Collisions of Multiply Charged Projectiles with Biologically Relevant Molecules - Hans Jürgen Lüdde; Alba Jorge; Marko Horbatsch; Tom Kirchner (Atoms, 2020)
A model for the description of proton collisions from molecules composed of atoms such as hydrogen, carbon, nitrogen, oxygen and phosphorus (H, C, N, O, P) was recently extended to treat collisions with multiply charged ions with a focus on net ionization. Here we complement the work by focusing on net capture. The ion–atom collisions are computed using the two-center basis generator method. The atomic net capture cross sections are then used to assemble two models for ion–molecule collisions: An independent atom model (IAM) based on the Bragg additivity rule (labeled IAM-AR), and also the so-called pixel-counting method (IAM-PCM) which introduces dependence on the orientation of the molecule during impact. The IAM-PCM leads to significantly reduced capture cross sections relative to IAM-AR at low energies, since it takes into account the overlap of effective atomic cross sectional areas. We compare our results with available experimental and other theoretical data focusing on water vapor (<semantics>H2O</semantics>), methane (<semantics>CH4</semantics>) and uracil (<semantics>C4H4N2O2</semantics>). For the water molecule target we also provide results from a classical-trajectory Monte Carlo approach that includes dynamical screening effects on projectile and target. For small molecules dominated by a many-electron atom, such as carbon in methane or oxygen in water, we find a saturation phenomenon for higher projectile charges (<semantics>q=3</semantics>) and low energies, where the net capture cross section for the molecule is dominated by the net cross section for the many-electron atom, and the net capture cross section is not proportional to the total number of valence electrons.